Aplikasi Gadai Syariah Dalam Perbankan - Nyimas Lidya Putri (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2019)
In human society life is always related to each other, in Islam it is recommended to help each other help in kindness and lighten the burden of others usually in the form of gifts or loans accompanied by collateral (mortgage / rahn). Pawn or rahn is a contract carried out by someone who wants to owe someone else, and he makes his property (in the form of immovable or movable goods) in his power, as collateral for debt until he repays his debt. The rights and obligations of the parties in a mortgage or rahn include: the pawn recipient has the right to sell marhun if rahin cannot fulfill his obligations at maturity, the pledge giver (rahin) has the right to return the mortgaged property after he repays his debt loan. In the pledge the pledge recipient has the right to control the object that was pawned to him as long as the pawning debt has not been paid off, but he has no right to use the pledge object without the permission of the owner. because in a mortgage that moves only the goods, the ownership status of the item does not move until maturity.